Modelling integral viscoelastic flows in OpenFOAM - Araújo, M. S. B. (2015)
[Excerpt] A large number of constitutive equations were developed for viscoelastic fluids, some empirical and other with strong physical foundations. The currently available macroscopic constitutive equations can be divided in two main types: differential and integral. Some of the constitutive equations, e.g. Maxwell are available both in differential and integral types. However, relevant in tegral models, like K - BKZ, just possesses the integral form. (...)